Organizational climate among healthcare personnel and satisfaction of users assisted by the Mobile Emergency Care Service (SAMU) in the context of COVID-19, Piura, 2021 - Guerra Elera, Fernanda Belén (2023)
Objective: To determine the relationship between the organizational climate among healthcare personnel and the satisfaction of users assisted by the Mobile Emergency Care Service (SAMU) in the context of COVID-19, Piura. Materials and methods: A Likert-scale survey was administered to 80 healthcare workers to assess the organizational climate and 110 SAMU users to assess their satisfaction level and whether they met the selection criteria. The survey hadone section addressed to SAMU workers and another one to SAMU users. Results: Out of all healthcare personnel, 51.3 % were men with an average age of 32.65 ± 6.8 % years, and there were moreregistered nurses (32.50 %) than doctors (31.30 %). Out of all users, 54.5 % were men with an average age of 58.78 ± 20.97 years, 57.3 % had no comorbidities and 84.5 % used the service once. The organizational climate and its dimensions showed healthy outcomes (96.58 ± 3.21). Most SAMU users (51.60 %) were satisfied (57/110) while 38.20 % (42/110) were moderately satisfied and 10.20 % (11/110) showed dissatisfaction. The main hypothesis concerning the relationship between the organizational climateand the satisfaction of SAMU users (p < 0.005) was confirmed. Moreover, there was a relationship between the five dimensions and the satisfaction of users.  Conclusions: There is a relationship between the organizational climate among SAMU healthcare workers and the satisfaction of SAMU users in Piura. The organizational climate and its dimensions, compared to the instrument developed by MINSA, showed healthy outcomes. Most patients were satisfied with the care received and the most frequent comorbidities were hypertension and type 2 diabetes mellitus.